Preparation method and application of long-circulation sodium ion battery positive electrode material

NaFe1-xⅡxO2-yⅦy material with O3 layered structure was prepared through hydrothermal technology. Using the second main group metal and the seventh main group non-metal elements, the electrochemical inactive and high-temperature treatment in the synthesis of sodium ion battery positive electrode materials was solved. The problem is that efficient charge transmission and stability are achieved, reducing costs and energy consumption.

CN119252856APending Publication Date: 2025-01-03NINGBO VEKEN BATTERY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411154706.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-22
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The existing sodium ion battery cathode materials are electrochemically inactive due to improper selection of Fe and Na sources during the synthesis process, and high-temperature treatment increases energy consumption, affecting the cycle life and cost-effectiveness of the battery.

Method used

The NaFe1-xⅡxO2-yⅦy material with O3-type layered structure was prepared by hydrothermal technology. By introducing the second main group metal elements and the seventh main group non-metal elements, such as Be, Mg, Ca, Sr, F, Cl, Br, Optimize material structure to improve electrochemical properties and stability.

Benefits of technology

It achieves efficient charge transfer and battery stability, reduces preparation costs, reduces harmful substance emissions, extends the cycle life of the battery, and reduces energy consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005004612240000091
    Figure BDA0005004612240000091
Patent Text Reader

Abstract

The invention belongs to the technical field of sodium-ion battery positive electrode materials, and relates to a preparation method and application of a long-circulation sodium-ion battery positive electrode material. The sodium ion battery positive electrode material is of an O3 type layered structure, the general formula of the sodium ion battery positive electrode material is NaFe < 1-x > II < x > O < 2-y > VII < y >, II is a second main group element, VII is a seventh main group element, x is more than 0 and less than or equal to 0.5, and y is more than or equal to 0.1 and less than or equal to 0.4. The single-phase and well-crystallized O3-NaFeO2 derivative is successfully prepared, shows a highly-ordered crystal structure, and is beneficial to efficient transmission of charges as a sodium-ion battery positive electrode material. Second main group metal elements and seventh main group non-metal elements are introduced into the structure of the material, so that the material shows excellent electrochemical performance, and the stability and efficiency of the prepared battery in the charging and discharging process are enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of positive electrode materials for sodium ion batteries and relates to a preparation method and application of a positive electrode material for a long-cycle sodium ion battery. Background Art

[0002] Sodium-ion batteries (SIBs) have become a strong competitor to lithium-ion batteries in the field of large-scale energy storage due to their low cost and global abundance of sodium resources. As a key component of SIBs, the performance of cathode materials directly determines the electrochemical properties of the battery. + The size is larger than Li + Larger, ideal cathode materials must have efficient Na + Diffusion channels and excellent structural stability ensure high efficiency and long life of the battery.

[0003] Layered sodium transition metal oxides (Na x MeO2, where Me represents a transition metal, is considered a strong candidate for the cathode material of solid oxide fuel cells and sodium ion batteries due to its low manufacturing cost and high theoretical specific capacity. This type of material presents a variety of layered polymorphs, among which O3-NaFeO2 has received special attention due to its abundant, non-toxic and low-cost iron source. In fact, many traditional layered cathode materials can be regarded as derivatives of O3-NaFeO2 with R-3m space group, including but not limited to LiCoO2, LiNi 0.5 Mn 0.5 O2、LiNi 1 / 3 Mn 1 / 3 Co 1 / 3 O2、Na x MeO2, etc., all belong to this category.

[0004] Under the current background, the challenge faced in synthesizing O3-NaFeO2 is that improper selection of Fe and Na sources may lead to the formation of electrochemically inactive NaFeO2, thus making the preparation complicated. The prior art discloses the synthesis of O3-NaFeO2 using Fe2O3 with low reaction activity as raw material and Na2O2 as sodium source, and the synthesis process requires to be carried out in an inert gas environment, which not only increases the cost, but also when O3-NaFeO2 is circulated at a higher voltage, it is easy to cause oxygen evolution reaction due to structural changes, releasing a large amount of gas, which seriously affects the cycle life of the battery. In addition, the preparation of positive electrode materials for sodium ion batteries often requires long-term high-temperature treatment, which further increases energy consumption, and therefore it is urgently necessary to optimize the cost.

[0005] In view of the above problems, researchers are working to develop low-cost, high-voltage, and long-cycle-life O3-NaFeO2 analogs as high-performance cathode materials for sodium-ion batteries. The goal is to achieve higher mass specific capacity and improve cycle stability by optimizing the material structure, ultimately promoting the commercialization of sodium-ion battery technology and meeting the needs of large-scale energy storage systems for cost-effective and environmentally friendly energy storage solutions. Summary of the invention

[0006] The present invention aims at the problems existing in the positive electrode materials of sodium ion batteries in the prior art and provides a preparation method and application of a positive electrode material for a long-cycle sodium ion battery.

[0007] The first object of the present invention is achieved by the following technical solutions:

[0008] A long-cycle sodium ion battery positive electrode material, the sodium ion battery positive electrode material is an O3 type layered structure, and its general formula is NaFe 1-x Ⅱ x O 2-y VII y , where II is the second main group element, VII is the seventh main group element, 0<x≤0.5, 0.1≤y≤0.4.

[0009] II is the second main group element, which can be listed as one or more elements of Be, Mg, Ca, Sr, Ba, and Ra.

[0010] Ⅶ is a seventh main group element, which can be one or more elements selected from F, Cl, Br, I, and At.

[0011] More preferably, the sodium ion battery positive electrode material NaFe 1-x Ⅱ x O 2-y VII y Among them, II includes one or more elements of Be, Mg, Ca, and Sr, and VII includes one or more elements of F, Cl, and Br.

[0012] More preferably, the sodium ion battery positive electrode material NaFe 1-x Ⅱ x O 2-y VII y Among them, II is Ca element and VII is F element.

[0013] The long-cycle sodium ion battery positive electrode material provided by the present invention is a positive electrode material with an O3-type layered structure. O3 is a specific arrangement of layered oxides, which is characterized by having a large space between layers and being able to accommodate sodium ions (Na + )’s embedding and de-embedding, thus realizing the charging and discharging process of the battery.

[0014] The second object of the present invention is achieved by the following technical solutions:

[0015] A method for preparing a long-cycle sodium ion battery positive electrode material, the preparation method comprising the following steps:

[0016] (1) adding sodium salt, iron salt, metal salt containing II and sodium salt containing VII into a solvent and stirring to dissolve, and recording the mixed solution as S1;

[0017] (2) Stirring the S1 solution to adjust the pH, pouring it into the inner lining of the reactor and maintaining it at a constant temperature for a period of time; after cooling, washing it with an organic solvent and water, and drying it to obtain the M1 sample;

[0018] (3) The M1 sample was pre-calcined and then heated to high temperature to obtain the target product O3-NaFe 1-x Ⅱ x O 2-y VII y .

[0019] Preferably, in step (1), the sodium salt includes one or more of sodium acetate, sodium nitrate, sodium acetate, sodium carbonate, sodium oxalate, and sodium carbonate. More preferably, sodium acetate is used.

[0020] Preferably, in step (1), the iron salt includes one or more of ferric acetate, ferric chloride, ferric oxalate, ferric acetate, ferric sulfate, and ferric nitrate. More preferably, ferric acetate is used.

[0021] Preferably, in step (1), the metal cation in the II metal salt is a second main group metal element, including one or more of calcium acetate, magnesium acetate, calcium nitrate, magnesium nitrate, calcium sulfate, magnesium sulfate, calcium carbonate, magnesium carbonate, calcium chloride, and magnesium chloride. Calcium acetate is more preferred.

[0022] Preferably, in step (1), the anion in the sodium salt containing VII is a non-metallic element of the seventh main group, including one or more of sodium fluoride, sodium chloride, and sodium bromide. More preferably, sodium fluoride is used.

[0023] Preferably, in step (1), the sodium salt, iron salt, II metal salt and VII sodium salt are added in a stoichiometric molar ratio of 1: (0.5-0.9): (0.1-0.5): (0.1-0.4) according to the general chemical formula of the target product.

[0024] Preferably, in step (1), the solvent comprises one or more of water, methanol, ethanol, isopropanol, acetone, tetrahydrofuran, ethyl acetate, acetonitrile, dimethylformamide, and dimethyl sulfoxide.

[0025] Preferably, in step (2), the pH of the S1 solution is adjusted to 7-10.

[0026] Preferably, in step (2), the reagent for adjusting pH includes one or more of sodium hydroxide, potassium hydroxide, aqueous ammonia, and acetic acid-sodium acetate buffer solution.

[0027] Preferably, in step (2), the S1 solution poured in accounts for 50-85% of the lining capacity of the reactor.

[0028] Preferably, in step (2), the constant temperature is 120-180° C., and the constant temperature is maintained for 10-20 hours.

[0029] Preferably, in step (2), the cooling temperature is 30-60°C.

[0030] Preferably, in step (2), the organic solvent includes one or more of alcohol organic matter, ether organic matter, and N-methylpyrrolidone.

[0031] Preferably, the alcohol organic compound may be one or more of ethanol, methanol, isopropanol, n-butanol, tert-butanol, ethylene glycol, and glycerol.

[0032] Preferably, the ether organic substance can be one or more of diethyl ether, dimethyl ether, phenethyl ether, butyl ether, ethylene glycol dimethyl ether, tetrahydrofuran, and dimethylnitrosamine.

[0033] Preferably, in the step (2), after cleaning, the mixture is placed in an oven for drying at a temperature of 70 to 110° C. and a drying time of 0.5 to 2 h.

[0034] Preferably, in step (3), the M1 sample is pre-calcined in a tubular furnace at a temperature of 200 to 400° C. for 1 to 5 hours.

[0035] Preferably, in step (3), the high temperature calcination temperature is 500-800° C. and the time is 5-10 hours.

[0036] Preferably, in step (3), the calcination atmosphere comprises a mixed gas of one or more of air, oxygen and carbon monoxide.

[0037] The third object of the present invention is achieved by the following technical solutions:

[0038] A long-cycle sodium-ion battery positive electrode plate comprises the long-cycle sodium-ion battery positive electrode material.

[0039] The fourth object of the present invention is achieved by the following technical solutions:

[0040] A long-cycle sodium-ion battery comprises the above-mentioned long-cycle sodium-ion battery positive electrode plate.

[0041] Compared with the prior art, the present invention has the following beneficial effects:

[0042] 1. The present invention provides a method for preparing a long-cycle sodium-ion battery positive electrode material. Through hydrothermal technology, a single-phase, well-crystallized O3-NaFeO2 derivative is successfully prepared. The obtained material exhibits a highly ordered crystal structure, which is conducive to the efficient transmission of charges.

[0043] 2. The present invention provides a long-cycle sodium-ion battery positive electrode material, which exhibits excellent electrochemical properties by introducing second-group metal elements and seventh-group non-metal elements into the structure, and the stability and efficiency of the material during the charge and discharge process are enhanced.

[0044] 3. The present invention provides a long-cycle sodium ion battery positive electrode material, which adds halogen elements represented by fluorine to the main structure, effectively improving the stability of the electrode material. This greatly enhances the electrochemical performance of the battery during long-term cycles, which means that the battery can still maintain good performance after multiple charge and discharge cycles, ensuring the long service life of the battery.

[0045] 4. The long-cycle sodium-ion battery positive electrode material provided by the present invention not only reduces the preparation cost, but also reduces the emission of harmful substances, thereby realizing green production.

[0046] 5. Based on the above performance improvement and cost-effectiveness, the long-cycle sodium-ion battery cathode material provided by the present invention has shown great application potential in the field of sodium-ion batteries. It is expected that in future energy storage solutions, this type of sodium-ion battery will play an important role and lead the development trend of a new generation of energy storage technology. DETAILED DESCRIPTION

[0047] The technical solution of the present invention is further described below in conjunction with specific embodiments. It should be understood that the specific embodiments described herein are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application.

[0048] Example 1

[0049] The method for preparing the long-cycle sodium ion battery positive electrode material prepared in this embodiment comprises the following steps:

[0050] (1) Sodium acetate, ferric acetate, calcium acetate and sodium fluoride were weighed in a molar ratio of Na:Fe:Ca:F=1:0.5:0.5:0.3, and then dissolved in 50 ml of deionized water and stirred evenly. The mixed solution was recorded as S1;

[0051] (2) After adjusting the pH value of the S1 solution to 8 using a 1 mol / L potassium hydroxide solution, the solution was stirred for 4 h; then poured into the polytetrafluoroethylene liner of the reactor, with the S1 solution accounting for 60% of the volume of the polytetrafluoroethylene liner, and kept at 160°C for 12 h; then washed with a mixture of NMP, ethanol and distilled water in sequence, and after washing, the sample was placed in an oven at 80°C and dried for 2 h to obtain the M1 sample;

[0052] (3) The M1 sample was pre-calcined at 300°C in a tube furnace for 2 h; then the temperature was raised to 650°C and calcined for 6 h to obtain the target product O3-NaFe 0.5 Ca 0.5 O 1.7 F 0.3 .

[0053] Example 2

[0054] The difference between this embodiment and embodiment 1 is that sodium acetate, ferric acetate, calcium acetate and sodium fluoride are weighed in corresponding amounts according to the molar ratio of Na:Fe:Ca:F=1:0.9:0.1:0.3 to obtain the target product O3-NaFe 0.9 Ca 0.1 O 1.7 F 0.3 , the rest is the same as in Example 1.

[0055] Example 3

[0056] The difference between this embodiment and embodiment 1 is that sodium acetate, ferric acetate, calcium acetate and sodium fluoride are weighed in corresponding amounts according to the molar ratio of Na:Fe:Ca:F=1:0.5:0.5:0.1 to obtain the target product O3-NaFe 0.5 Ca 0.5 O 1.9 F 0.1 , the rest is the same as in Example 1.

[0057] Example 4

[0058] The difference between this embodiment and embodiment 1 is that the S1 solution poured in accounts for 85% of the volume of the polytetrafluoroethylene liner, and the rest is the same as embodiment 1.

[0059] Example 5

[0060] The only difference between this embodiment and embodiment 1 is that the M1 sample is pre-calcined and then kept at a constant temperature for 4 hours. The rest is the same as embodiment 1.

[0061] Example 6

[0062] The difference between this embodiment and embodiment 1 is that the calcination is continued for 10 hours after the temperature is raised, and the rest is the same as embodiment 1.

[0063] Example 7

[0064] The only difference between this embodiment and embodiment 1 is that the pre-calcination temperature of the M1 sample is 400° C., and the rest is the same as embodiment 1.

[0065] Example 8

[0066] The difference between this embodiment and embodiment 1 is that the temperature is raised to 800° C. and the calcination is continued. The rest is the same as embodiment 1.

[0067] Example 9

[0068] The only difference between this embodiment and embodiment 1 is that 1 mol / L sodium hydroxide solution is used to adjust the pH value of the S1 solution, and the rest is the same as embodiment 1.

[0069] Example 10

[0070] The difference between this embodiment and embodiment 1 is that sodium acetate, ferric acetate, barium nitrate and sodium iodide are weighed in corresponding amounts according to the molar ratio of Na:Fe:Ba:I=1:0.5:0.5:0.3 to obtain the target product O3-NaFe 0.5 Ba 0.5 O 1.7 I 0.3 , the rest is the same as in Example 1.

[0071] Embodiment 11

[0072] The difference between this embodiment and embodiment 1 is that sodium acetate, ferric acetate, barium nitrate and sodium fluoride are weighed in corresponding amounts according to the molar ratio of Na:Fe:Ba:F=1:0.5:0.5:0.3 to obtain the target product O3-NaFe 0.5 Ba 0.5 O 1.7 I 0.3 , the rest is the same as in Example 1.

[0073] Example 12

[0074] The only difference between this embodiment and embodiment 1 is that sodium acetate, ferric acetate, calcium acetate and sodium iodide are weighed in corresponding amounts according to a molar ratio of Na:Fe:Ca:I=1:0.5:0.5:0.3 to obtain the target product O3-NaFe 0.5 Ba 0.5 O 1.7 I 0.3 , the rest is the same as in Example 1.

[0075] Comparative Example 1

[0076] The difference between this comparative example and Example 1 is that sodium acetate, ferric acetate, calcium acetate and sodium fluoride are weighed in corresponding amounts according to the molar ratio of Na:Fe:Ca:F=1:0.3:0.7:0.3 to obtain the target product O3-NaFe 0.3 Ca 0.7 O 1.7 F 0.3 , the rest is the same as in Example 1.

[0077] Comparative Example 2

[0078] The difference between this comparative example and Example 1 is that sodium acetate, ferric acetate, calcium acetate and sodium fluoride are weighed in corresponding amounts according to the molar ratio of Na:Fe:Ca:F=1:0.5:0.5:0.05 to obtain the target product O3-NaFe 0.5 Ca 0.5 O 1.95 F 0.05 , the rest is the same as in Example 1.

[0079] Comparative Example 3

[0080] The difference between this comparative example and Example 1 is that sodium acetate, ferric acetate, calcium acetate and sodium fluoride are weighed in corresponding amounts according to the molar ratio of Na:Fe:Ca:F=1:0.5:0.5:0.5 to obtain the target product O3-NaFe 0.5 Ca 0.5 O 1.5 F 0.5 , the rest is the same as in Example 1.

[0081] Comparative Example 4

[0082] The difference between this comparative example and Example 1 is that the S1 solution poured in accounts for 30% of the volume of the polytetrafluoroethylene liner, and the rest is the same as Example 1.

[0083] Comparative Example 5

[0084] The difference between this comparative example and Example 1 is that the M1 sample is pre-calcined and then kept at a constant temperature for 0.5 h. The rest is the same as Example 1.

[0085] Comparative Example 6

[0086] The difference between this comparative example and Example 1 is that the calcination is continued for 12 hours after the temperature is raised, and the rest is the same as Example 1.

[0087] Comparative Example 7

[0088] The difference between this comparative example and Example 1 is that the pre-calcination temperature of the M1 sample is 550° C., and the rest is the same as Example 1.

[0089] Comparative Example 8

[0090] The difference between this comparative example and Example 1 is that the temperature is raised to 1000° C. and the calcination is continued. The rest is the same as Example 1.

[0091] The positive electrode materials, conductive carbon black and PVDF binder prepared in Examples 1 to 11 and Comparative Examples 1 to 8 were mixed in a mass ratio of 90:5:5, and NMP solvent was added to form a positive electrode slurry, which was then coated on an aluminum foil. After vacuum drying at 100°C and rolling, a positive electrode sheet was obtained; then the positive electrode sheet, the counter electrode sheet (metallic sodium), the electrolyte (solute NaPF6, concentration 1 mol / L, solvent EC:DEC=1:1) and the glass fiber separator were assembled into a battery, and relevant battery performance tests were carried out. The specific test method is as follows.

[0092] 1. First Coulomb efficiency test

[0093] First, place the battery in a 25±2℃ environment for 8h, then charge it to 4.8V at a constant current of 0.05C, and record the resulting capacity as the 0.05C charging capacity. Then, let it stand for 5min, and then discharge it to 2.8V at a constant current of 0.1C, and record the resulting capacity as the 0.1C discharge capacity. Finally, stop the operation and calculate the first coulomb efficiency as follows:

[0094] First coulombic efficiency = 0.1C discharge capacity / 0.05C charge capacity.

[0095] 2. Discharge capacity test corresponding to current density of 2C

[0096] First, place the battery in a 25±2℃ environment for 8h, then charge it to 4.8V at 0.2C constant current, then let it stand for 5min, then discharge it to 2.8V at 0.2C constant current, record it as capacity C1, then let it stand for 5min, then charge it to 4.8V at 0.2C constant current, let it stand for 5min, then discharge it to 2.8V at 2C constant current, the obtained capacity is 2C, the corresponding discharge capacity is C2, calculate the discharge efficiency corresponding to 2C as follows:

[0097] The discharge efficiency corresponding to 2C = C2 / C1*100%.

[0098] 3. 0.5C cycle 400 cycles capacity test

[0099] First, place the battery in a 25±2℃ environment for 8h, then charge it to 4.8V at 0.5C constant current, then let it stand for 5min, then charge it at 4.8V constant voltage to 0.05C, let it stand for 5min, then discharge it to 2.8V at 0.5C constant current, repeat the above 400 times, and finally stop the operation, record the 1st and 400th cycle discharge capacity, and calculate the 400-cycle capacity retention rate as follows:

[0100] 400-cycle capacity retention rate = 400th-cycle discharge capacity / 1st-cycle discharge capacity.

[0101] Table 1 Battery performance test results

[0102]

[0103] It can be found from Examples 1, 2 and Comparative Example 1 that II doping can affect the first efficiency, cycle, rate, etc. of the battery, while excessive doping is not conducive to the performance of the material.

[0104] It can be found from Examples 1 and 3 and Comparative Examples 2 and 3 that increasing the VII doping content within a certain range can greatly improve the oxygen evolution reaction and help to improve the material's cycle performance, while too low or too high a VII doping content is not conducive to the performance of battery capacity, first efficiency and other performance.

[0105] It can be found from Examples 1, 4 and Comparative Example 4 that the volume ratio of the material inside the reactor has an important influence on the internal synthetic material. Increasing the ratio of S1 solution to the volume of the polytetrafluoroethylene lining (volume ratio) within the technical scope of the present invention is beneficial to the particle growth of the material, increases the growth of the material crystal, and improves the battery performance; on the contrary, if the volume ratio is too low, the material particles formed inside are smaller during the high-temperature reaction process, which is not conducive to the initial efficiency and long-cycle performance of the battery.

[0106] From Examples 1, 5 to 8 and Comparative Examples 5 to 8, it can be seen that the preheating reaction time, high temperature calcination time, preheating reaction temperature and high temperature calcination temperature of the material are explored, and it is found that these temperatures and times have a great influence on the material performance. Specifically, the preheating reaction can rapidly transform the material structure and affect the first effect and cycle of the battery. The longer preheating time (Examples 1 and 5) can be carried out in a coherent manner with the subsequent high temperature treatment to improve the battery performance. On the contrary, the preheating time is too short (Comparative Example 5) and the improvement effect cannot be achieved; the preheating temperature within the technical range (Examples 1 and 7) has good battery performance. In order to reduce costs, a lower preheating temperature can be used, and an excessively high preheating temperature (Comparative Example 7) will affect the synthesis of the material; a higher calcination temperature (Examples 1 and 8) and an extended calcination time (Examples 1 and 6) are conducive to the growth of material crystals, which will improve the battery performance; however, an excessively long calcination time (Comparative Example 6) and an excessively high calcination temperature (Comparative Example 8) will cause material cracking, excessive material hardness, and high costs, thereby affecting the performance of the battery.

[0107] It can be found from Examples 1 and 9 that using different reagents to adjust the pH of the material has little effect on the battery performance.

[0108] From Examples 1, 10 to 12, it can be seen that different II and VII doping were used in the positive electrode materials of sodium ion batteries, and it was found that the II and VII elements within the scope of the technical solution of the present invention can have good battery performance. It was further found that the sodium ion battery prepared by doping with the preferred Ca and F elements of the present invention can have better battery efficiency and long cycle performance.

[0109] The various aspects, embodiments, and features of the present invention should be considered to be illustrative in all aspects and not limiting of the present invention, the scope of which is defined solely by the claims. Other embodiments, modifications, and uses will be apparent to those skilled in the art without departing from the spirit and scope of the claimed invention.

[0110] In the preparation method of the present invention, the order of each step is not limited to the order listed. For those skilled in the art, without creative work, the order of each step is also within the protection scope of the present invention. In addition, two or more steps or actions can be performed simultaneously.

[0111] Finally, it should be noted that the specific embodiments described herein are merely examples of the present invention, and are not intended to limit the implementation methods of the present invention. A person skilled in the art of the present invention may make various modifications or supplements to the specific embodiments described, or replace them in a similar manner. It is not necessary and impossible to provide all examples of all implementation methods here. However, these obvious changes or modifications derived from the essential spirit of the present invention still fall within the scope of protection of the present invention, and interpreting them as any additional limitation is contrary to the spirit of the present invention.

Claims

1. A long cycle sodium ion battery positive electrode material, characterized in that: The positive electrode material of the sodium ion battery is an O3-type layered structure, and its general formula is NaFe 1-x Ⅱ x O 2-y VII y , where II is the second main group element, VII is the seventh main group element, 0<x≤0.5, 0.1≤y≤0.

4.

2. A long cycle sodium ion battery positive electrode material according to claim 1, characterized in that: The sodium ion battery positive electrode material NaFe 1-x Ⅱ x O 2-y VII y Among them, II includes one or more elements selected from Be, Mg, Ca, Sr, Ba, and Ra, and VII includes one or more elements selected from F, Cl, Br, I, and At.

3. The long cycle sodium ion battery positive electrode material according to claim 1, characterized in that: The sodium ion battery positive electrode material NaFe 1-x Ⅱ x O 2-y VII y Among them, II is Ca element and VII is F element.

4. A method for preparing a long-cycle sodium ion battery positive electrode material according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: (1) adding sodium salt, iron salt, metal salt containing II and sodium salt containing VII into a solvent and stirring to dissolve, and recording the mixed solution as S1; (2) Stirring the S1 solution to adjust the pH, pouring it into the inner lining of the reactor and maintaining it at a constant temperature for a period of time; after cooling, washing it with an organic solvent and water, and drying it to obtain the M1 sample; (3) The M1 sample was pre-calcined and then heated to high temperature to obtain the target product O3-NaFe 1-x Ⅱ x O 2-y VII y .

5. The method for preparing a long cycle sodium ion battery positive electrode material according to claim 4, characterized in that: In the step (1), the sodium salt includes one or more of sodium acetate, sodium nitrate, sodium acetate, sodium carbonate, sodium oxalate, and sodium carbonate; And / or, the iron salt includes one or more of ferric acetate, ferric chloride, ferric oxalate, ferric acetate, ferric sulfate, and ferric nitrate; And / or, the metal cation in the II-containing metal salt is a metal element of the second main group, including one or more of calcium acetate, magnesium acetate, calcium nitrate, magnesium nitrate, calcium sulfate, magnesium sulfate, calcium carbonate, magnesium carbonate, calcium chloride, and magnesium chloride; And / or, the anion in the sodium salt containing VII is a non-metallic element of the seventh main group, including one or more of sodium fluoride, sodium chloride, and sodium bromide.

6. The method for preparing a long cycle sodium ion battery positive electrode material according to claim 4, characterized in that: In the step (1), the sodium salt, iron salt, II metal salt and VII sodium salt are added in a stoichiometric molar ratio of 1: (0.5-0.9): (0.1-0.5): (0.1-0.4) according to the general chemical formula of the target product.

7. The method for preparing a long cycle sodium ion battery positive electrode material according to claim 4, characterized in that: In the step (2), the pH of the S1 solution is adjusted to 7-10; And / or, the pH adjusting agent includes one or more of sodium hydroxide, potassium hydroxide, ammonia water, and acetic acid-sodium acetate buffer solution; and / or, the poured S1 solution accounts for 50-85% of the lining capacity of the reactor; And / or, the constant temperature is 120-180° C., and the constant temperature is maintained for 10-20 hours; And / or, the cooling temperature is 30-60°C; And / or, the organic solvent includes one or more of alcohol organic matter, ether organic matter, and N-methylpyrrolidone; And / or, after cleaning, put it into an oven for drying, the drying temperature is 70-110° C., and the drying time is 0.5-2 h.

8. The method for preparing a long cycle sodium ion battery positive electrode material according to claim 4, characterized in that: In the step (3), the M1 sample is pre-calcined in a tube furnace at a temperature of 200 to 400° C. for 1 to 5 hours; And / or, the high temperature calcination temperature is 500-800°C and the time is 5-10h; And / or, the calcination atmosphere includes one or more mixed gases of air, oxygen, and carbon monoxide.

9. A long cycle sodium ion battery positive electrode plate, characterized in that: It comprises a long cycle sodium ion battery positive electrode material as described in any one of claims 1 to 3.

10. A long cycle sodium ion battery, characterized in that: It comprises a long cycle sodium ion battery positive electrode plate as described in claim 9.